PEMAHAMAN MENDENGARKAN DALAM SASTRA: PENGGUNAAN ALAT BANTU VISUAL OLEH SISWA EFL DALAM INTERPRETASI PUISI - Kurnia Devi Yuswandari; Nur Aida Fitriyah (Mastery: Master of English Language Journal, 2024)
This study explores the use of visual aids on listening comprehension in poetry interpretation among EFL students. It employs a descriptive qualitative research design. The participants of this study are fourth-semester students of the English Department at STIT Miftahul Midd Lumajang. In order to gain the data, it uses semi-structured interviews and classroom observations. The findings indicate that visual aids profoundly elevate student engagement with poetic texts by making abstract concepts more accessible and relatable. The participants of this study reported that these resources not only fostered emotional connections to the material but also encouraged active participation and collaborative discussions. Additionally, visual aids were found to promote cultural awareness, enriching students’ understanding of the literary themes explored in poetry. Overall, this research highlights the transformative potential of visual aids in enhancing the educational experience of EFL students, paving the way for more effective teaching practices. The study advocates for the integration of visual aids into EFL literature instruction to improve comprehension and appreciation of complex texts.